EFEKTIVITAS PEMUNGUTAN PAJAK HOTEL DAN RESTORAN PADA PEMERINTAH DAERAH KOTA DENPASAR - Intan Yuliartini, Putu; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 10 No 2 (2015), 2015)
The Indonesian government imposed a policy of regional autonomy with the aim to facilitate local governments regulate local affairs independently. Denpasar City is one of the areas that implement decentralization policy and requires a lot of funds to finance local development. The biggest potential held in the Denpasar area of financing comes from tax expenditures hotels and restaurants and are expected to provide the largest contribution in the PAD. This study aims to determine the effectiveness of tax collection rate hotels and restaurants and their contribution to PAD Denpasar. Methods of data collection in this study is the observation nonparticipant. The variable in this study is the ratio of the effectiveness and contribution analysis. Data analysis in this study is a quantitative analysis. Based on the analysis, the average effective tax collection hotels and restaurants in the city of Denpasar years 2009-2013 amounted to 113.54 percent categorized as very effective, and the average contribution of tax revenue hotels and restaurants in the city of Denpasar in 2009 to 2013 by 32 , 27 percent of the category quite well.
Keywords: effectiveness, contribution, hotel and restaurant tax, local revenue